New-Onset Lichen Planus Induced by the Pfizer COVID-19 Vaccine - Fadi A. Alghamdi; Shahad T. Khayyat; Mohammed M. Alshareef; Wala’a Felemban (Case Reports in Dermatological Medicine)
Objective. Coronavirus disease 2019 (COVID-19) vaccine distribution continues to expand; however, increased cutaneous reactions have been reported. Several recent studies suggest a link between COVID-19 vaccination and the development of various cutaneous complications. Lichen planus is a chronic, immune-mediated, inflammatory dermatological illness with an unclear etiology. In this case report, we assessed the relationship between COVID-19 vaccination (Pfizer) and lichen planus diagnosis and evaluated the link between additional doses of the vaccine and disease progression. Methods. Complete clinical, laboratory, and histopathological assessment of a patient was performed with ethical and privacy considerations. Written informed consent for all clinical data, images, and publication was obtained from the patient. Results. New-onset lichen planus appeared 48 hours after the first dose of the Pfizer vaccine. The symptoms worsened following the second dose. The patient responded gradually to topical corticosteroids, and lichen planus was controlled within 21 days. Conclusion. Our case significantly contributes to the literature by highlighting that additional doses of the Pfizer vaccine can contribute to disease progression. Therefore, reporting the patient’s condition associated with COVID-19 vaccination should be considered. Future studies should be performed to investigate the combined onset of lichen planus and multisystem COVID-19 vaccine-related complications.